Becoming first time father of premature newborn during the first wave of the pandemic: a case study approach - Jean-Dit-Pannel, Romuald; Dubroca, Chloé; Koliouli, Flora (Frontiers in Psychology, 2024)
Introduction The aim of this paper is to delve into the emotional and psychological challenges that fathers face as they navigate the complexities of having a preterm infant in the NICU and in an unprecedented sanitary context. Methods We used three data collection methods such as interviews (narrative and the Clinical Interview for Parents of High-risk Infants- CLIP) and the Edinburgh Postnatal Depression Scale (EPDS) to gain a comprehensive understanding of the cases. Results The following analysis explores two individuals’ personal experiences of becoming a first-time father during the first wave of the COVID-19 pandemic through a close examination of two superordinate themes: “A series of separations through the experienced COVID- 19 restrictions” and “Moments of connection.” The transition to fatherhood is essentially with a medicalized form of connection with their newborn and the perceived paternal identity. In terms of temporality, these fathers experienced a combination of concerns about their infants’ long-term development and COVID-19 health concerns. Furthermore, they showed indications of phobic or hypochondriac tendencies using a psychoanalytic framework, along with an increased risk of postpartum depression.